2018
DOI: 10.1002/aoc.4355
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐ and binuclear nickel catalysts for 1‐hexene polymerization

Abstract: Polymerization of 1-hexene was carried out using a mononuclear (MN) catalyst and two binuclear (BN 1 and BN 2 ) α-diimine Ni-based catalysts synthesized under controlled conditions. Ethylaluminium sesquichloride (EASC) was used as an efficient activator under various polymerization conditions. The highly active BN 2 catalyst (2372 g poly(1-hexene) (PH) mmol −1 cat) in comparison to BN 1 (920 g PH mmol −1 cat) and the MN catalyst (819 g PH mmol −1 cat) resulted in the highest viscosity-average molecular weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 73 publications
(131 reference statements)
2
26
0
Order By: Relevance
“…Molecular weight distributions (MWDs) were determined with a Polymer Char high-temperature gel permeation chromatography (GPC) instrument, run at 145°C under a flow of 1,2,4-trichlorobenzene at a rate of 1 ml min −1 . [51,52] The catalysts studied were mononuclear (M 1 and M 2 ) and dinuclear (C 1 -C 6 ) Ni α-diimine-based catalysts. [49] 13 C NMR spectra of polyethylene were recorded with a Bruker AC-400 MHz instrument at 115°C in deuterated tetrachloroethane with tetramethylsilane as an internal standard.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular weight distributions (MWDs) were determined with a Polymer Char high-temperature gel permeation chromatography (GPC) instrument, run at 145°C under a flow of 1,2,4-trichlorobenzene at a rate of 1 ml min −1 . [51,52] The catalysts studied were mononuclear (M 1 and M 2 ) and dinuclear (C 1 -C 6 ) Ni α-diimine-based catalysts. [49] 13 C NMR spectra of polyethylene were recorded with a Bruker AC-400 MHz instrument at 115°C in deuterated tetrachloroethane with tetramethylsilane as an internal standard.…”
Section: Characterizationmentioning
confidence: 99%
“…[53] This effect also implies the steric and electronic impacts of ligand architecture and metal center. [52] This suggested that the presence of acenaphthene could make the active center to be a better π-acceptor. The effect of backbone was observed for catalysts M 2 and C 4 in comparison to M 1 and C 3 , respectively.…”
Section: Ethylene Polymerization Catalyzed By Mononuclear and Dinucmentioning
confidence: 99%
“…[45] Herein, two dinuclear α-diimine Ni catalysts (BNC1 and BNC2) along with their mononuclear analogues (MNC1 and MNC2) were selected based on their significant catalytic behavior and polymer properties (Scheme 1). [44,[46][47][48] To clarify, based on our previous reports, BNC1 showed the highest activity among the dinuclear structures studied in homopolymerization of ethylene and α-olefins, whereas BNC2 made polyolefins at a moderate productivity. [44,47] BNC1 also produced PE with high molecular weight and high selectivity for hexyl branches, whereas BNC2 made an ethylenepropylene copolymer (with high level of methyl branches) using only ethylene as feed.…”
Section: Introductionmentioning
confidence: 87%
“…However, higher stability of dinuclear catalyst led to higher activity in comparison with its mononuclear counterpart. [46,47,56] On the other side, the lowest activity was observed in the masked method. It could be suggested that increasing of organoaluminium (TiBA) in the reaction may prevent the monomer coordination into the catalyst active centers.…”
Section: Effect Of Different Cocatalyst On the Activity Of Bnc1 Formentioning
confidence: 94%
“…The results were mainly included highly branched ethylene‐MM copolymers with high molar mass, [24,25] depending on MM incorporation into cocatalyst type, cocatalyst/MM ratio [6,26] and catalyst structure [27] . On the other side, multinuclear late transition metal (LTM) catalysts as well as mononuclear analogues are important due to their superior catalytic properties [2,28–32] …”
Section: Introductionmentioning
confidence: 99%